Chemical contributions to silicon anode calendar aging are dominant over mechanical contributions - McBrayer, Josefine D.; Harrison, Katharine L.; Allcorn, Eric; Minteer, Shelley D. (Frontiers in Batteries and Electrochemistry, 2023)
Silicon (Si) anodes are a promising candidate for increasing the energy density of lithium (Li)-ion batteries for electric vehicles. However, they have recently been identified as having poor calendar life that is insufficient for commercial needs, in addition to the well-known issue of their poor cycle life resulting from large volume expansion. Here, a specially designed protocol with variable rest periods between intermittent cycling is used to evaluate the impact of the mechanical disruption of Si and solid electrolyte interphase (SEI) from cycling on calendar aging measurements. Si was found to undergo more mechanical degradation during calendar aging with intermittent cycling than graphite. However, Si anode capacity fade was still dominated by time, especially for rest periods greater than or equal to 1 month between cycling. Postmortem dQ/dV half-cell analysis indicated this was mainly due to Li inventory loss and an increase in electrode resistance. Isothermal microcalorimetry further demonstrated that Si passivation is more disrupted than graphite passivation with intermittent cycling and suggested that there may be a chemical buildup of a detrimental species in the electrolyte, leading to a large spike in heat after the Si and SEI are disrupted by cycling.